Can Chinese students make a rational decision when choosing university and university course? - Niu, Lili (2007)
More and more Chinese students are coming to UK for their higher education; this can be called as education consumption. For this consumption, the first decision the consumers need to make is choosing a university and course they are going to attend, just like which products they are going to buy. However, during this process, whether this consumption is rational or irrational for these overseas students; how and what factors influenced their decision making process are the core issues to research. This paper used the theory of consumer's psychology and the theory of decision making process, and also based on the statistics models to examine these problems. It states that the Chinese students consumption psychology is strongly influenced by Chinese culture; and the output of this paper also proved the Chinese students whether can make rational consumption and make good decision depends on their learning purpose and learning motivation. The clear purpose and strong motivation will make the Chinese students, or called consumers, to set and follow a comprehensive decision making process before choosing university and course. All of these researches help to understand Chinese students' consumption psychology when doing education consumption, and also help Chinese students, to preview or review their behaviors of choosing their universities and course.